Transcription factors in macrophage differentiation - Sieweke, Michael (Henry Stewart Talks, 2012)
Control of cellular identity and cell numbers, Gain and loss of function approaches, Transcription factor/cytokine interplay, Mechanism: transcription factor levels, balance and combinatorial control, Enhancer definition of macrophage identity, Differentiation and cell cycle control